Effects of Three Different Withering Treatments on the Aroma of White Tea - Huiting Wu; Yuyu Chen; Wanzhen Feng; Shanshan Shen; Yuming Wei; Huiyan Jia; Yujie Wang; Weiwei Deng; Jingming Ning (Foods, 2022)
White tea (WT) is a slightly fermented tea, and withering is a critical step in its processing. The withering treatment can affect white tea’s aroma; different treatments’ effects were investigated in this study. White tea was withered indoors (IWT), in a withering-tank (WWT), or under sunlight (SWT). Quantitative descriptive analysis (QDA) results showed that SWT had a more obvious flower aroma, and WWT had a more pronounced grassy aroma. Volatile compounds were extracted and subsequently detected with solvent-assisted flavor evaporation (SAFE) and headspace solid-phase microextraction (HS-SPME) combined in addition to gas chromatography–mass spectrometry (GC-MS). A total of 202 volatile compounds were detected; 35 of these aroma-active compounds met flavor dilution (FD) factor ≥ 4 or odor activity value (OAV) ≥ 1. The nine key potent odorants for which both conditions were met were dimethyl sulfide, 2-methyl-butanal, 1-penten-3-one, hexanal, (Z)-4-heptenal, β-Myrcene, linalool, geraniol, and trans-β-ionone. These results were used with QDA to reveal that SWT had a stronger floral aroma mainly due to an increase of geraniol and linalool. Moreover, WWT had a stronger grassy aroma mainly due to increased hexanal. The results could be used to select processing methods for producing white tea with a superior aroma.